Integrating Contextual Learning, STEAM, and Virtual Reality in Geometry: An Investigation of Implementation and Challenges in South Sumatera - Sari, Novita; Aisyah, Nyimas; Susanti, Ely (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
Geometry is a fundamental branch of mathematics that supports the development of logical thinking, spatial reasoning, and problem-solving skills. Yet, many students still struggle to understand geometric concepts because learning remains abstract and lacks meaningful real-world connections. In Indonesia, geometry instruction often emphasizes procedural mastery over deep conceptual understanding, underscoring the need for innovative approaches that make learning more concrete and engaging. Integrating real-world contexts, the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach, and Virtual Reality (VR) technology offers a promising way to bridge the gap between abstract ideas and practical applications. This study investigates the extent of implementation and the challenges in applying contextual, STEAM-based, and VR-supported geometry learning in Indonesia. Participants included 100 junior high school students and 10 mathematics teachers, randomly selected from South Sumatera, a region whose Gambo Muba textile tradition provides a culturally relevant context for geometry learning. Using a mixed-methods design, data were collected through questionnaires, interviews, and classroom observations. Findings show that STEAM-based and VR-supported learning positively influences students’ conceptual understanding, motivation, and engagement, particularly in geometric transformations. However, implementation remains at an early stage, with teachers displaying positive attitudes but limited experience, and with constraints on VR availability and training. The study underscores the need for capacity building and improved infrastructure to optimize this innovative approach.